2013
DOI: 10.1039/c3cp50376c
|View full text |Cite
|
Sign up to set email alerts
|

Solution behaviors and microstructures of PNIPAm-P123-PNIPAm pentablock terpolymers in dilute and concentrated aqueous solutions

Abstract: The solution behaviors and microstructures of poly(N-isopropylacrylamide)x-poly(ethylene oxide)20-poly(propylene oxide)70-poly(ethylene oxide)20-poly(N-isopropylacrylamide)x (PNIPAmx-PEO20-PPO70-PEO20-PNIPAmx or PNIPAmx-P123-PNIPAmx) pentablock terpolymers with various PNIPAm block lengths in dilute and concentrated aqueous solutions were investigated by micro-differential scanning calorimetry (micro-DSC), static and dynamic light scattering (SLS & DLS), and synchrotron small angle X-ray scattering (SAXS). Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 55 publications
3
37
0
Order By: Relevance
“…While rheology is more sensitive in terms of macromolecular phase behavior, it can also predict the secondary processes on a very short time scale. The rheologically derived LCST value for PNIPAM of 32 °C is in good agreement with the previously reported values …”
Section: Resultssupporting
confidence: 91%
“…While rheology is more sensitive in terms of macromolecular phase behavior, it can also predict the secondary processes on a very short time scale. The rheologically derived LCST value for PNIPAM of 32 °C is in good agreement with the previously reported values …”
Section: Resultssupporting
confidence: 91%
“…As the temperature was increased to 32 °C, the poly(NIPAAM- co -DMAAPS) solution with a monomer ratio of 100:0 (tube a) exhibited a color/turbidity change. This is consistent with previous studies [ 25 , 50 , 51 ], which reported that poly(NIPAAM) homopolymer chains undergo reversible collapse or swelling in aqueous solutions above or below their transition temperatures/LCSTs, which is approximately 32–34 °C for the co-polymer in the present study. Furthermore, the solutions with the NIPAAM:DMAAPS ratios of 95:5 (tube b), 90:10 (tube c), and 85:15 (tube d) exhibited turbidity at 41, 52, and 70 °C, respectively.…”
Section: Resultssupporting
confidence: 94%
“…21,22 The micellization and thermo-responsive behaviors of numerous PNIPAM-based BCPs have been extensively studied. [23][24][25][26][27][28][29][30] However, in most of the studies only the change in the micelle size without the alteration of the overall micellar morphology is reported. [31][32][33][34] Wu observed a transition of the micellar morphology from wormlike vesicles to spherical vesicles in dioxane/ethanol upon increasing the temperature for a PS-b-PNIPAM formed by hydrogen bonds at the end of both the blocks.…”
Section: Introductionmentioning
confidence: 99%